2018
DOI: 10.1021/acsnano.8b00528
|View full text |Cite
|
Sign up to set email alerts
|

Templated Assembly of a Functional Ordered Protein Macromolecular Framework from P22 Virus-like Particles

Abstract: Bottom-up construction of mesoscale materials using biologically derived nanoscale building blocks enables engineering of desired physical properties using green production methods. Virus-like particles (VLPs) are exceptional building blocks due to their monodispersed sizes, geometric shapes, production ease, proteinaceous composition, and our ability to independently functionalize the interior and exterior interfaces. Here a VLP, derived from bacteriophage P22, is used as a building block for the fabrication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 54 publications
1
80
1
Order By: Relevance
“…77 Such a reaction has also been demonstrated in P22 which is itself arranged into a higher order, superlattice structure. 64,[78][79][80]…”
Section: Bacteriophage P22mentioning
confidence: 99%
“…77 Such a reaction has also been demonstrated in P22 which is itself arranged into a higher order, superlattice structure. 64,[78][79][80]…”
Section: Bacteriophage P22mentioning
confidence: 99%
“…Previous work has shown that P22 and phage L behave similarly [33,34,36] and all of the amino acid substitutions found in phage L have even been identified occasionally in P22 stocks as phenotypically silent mutations (Teschke lab, unpublished data). Lastly, as Dec bound to P22 is a widely used system for a variety of nanomaterials applications [10,42,43], identifying key residues that contribute to Dec interactions with P22 is highly useful for practical applications. Therefore, we felt it reasonable to use the established genetics of P22 as a model for the native phage L for our mutagenesis studies.…”
Section: Resultsmentioning
confidence: 99%
“…[ 50–52 ] Moreover, the assembly of VLPs can be promoted, templated, and even controlled by heterologous biomolecules, organic molecules (e.g., polymers), or inorganic NPs with the appropriate features (e.g., a negative charge to promote the assembly of VLPs with a positively charged inner surface). [ 53–56 ] Three basic general strategies for capsid assembly are recognized ( Figure ): i) capsid self‐assembly, ii) scaffolding‐protein‐assisted capsid assembly, and iii) viral‐nucleic‐acid‐assisted capsid assembly.…”
Section: Vlp Production and Assemblymentioning
confidence: 99%
“…Virus‐like NPs are also used in applications such as RNA and enzyme delivery and protein supplementation. [ 55,80,118,149 ] MS2 VLPs displaying the TAT peptide on their surfaces effectively penetrated the cytomembrane and delivered microRNA‐122. The inhibitory effects of microRNA‐122 on hepatocellular carcinoma were significant in Hep3B, HepG2, and Huh7 cells and in Hep3B‐related animal models.…”
Section: Biomedical Applications Of Vlpsmentioning
confidence: 99%